Vologda Archbishop’s House of St. Sophia on the Eve of the Church Reform of Peter the Great - Nikita Bashnin (Historia provinciae: журнал региональной истории, 2020)
The article is devoted to the study of the census books of the patrimonies of the Vologda Archbishop’s House of St. Sophia in 1701–02. These documents appeared as a result of a large-scale inventory of the lands and property owned by the church within the framework of Church reforms of Peter the Great. The property of the House of St. Sophia was located in five uyezds and included 268 settlements where more than 6.5 thousand males lived. Eight monasteries and pustyns were added to the House around the 1700s. The census books not only contain information about social and economic history, but also provide the material for the study of icons and book collections of parish churches.